2005
DOI: 10.1093/jis/5.1.32
|View full text |Cite
|
Sign up to set email alerts
|

The broadly insecticidal Photorhabdus luminescens toxin complex a (Tca): Activity against the Colorado potato beetle, Leptinotarsa decemlineata, and sweet potato whitefly, Bemisia tabaci

Abstract: Toxin complex a (Tca), a high molecular weight insecticidal protein complex produced by the entomopathogenic bacterium Photorhabdus luminescens, has been found to be orally toxic to both the Colorado potato beetle, Leptinotarsa decemlineata, and the sweet potato whitefly, Bemisia tabaci biotype B. The 48 hour LC50 for Tca against neonate L. decemlineata was found to be 2.7 ppm, and the growth of 2nd instar L. decemlineata exposed to Tca for 72 hours was almost entirely inhibited at concentrations above 0.5 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…To our knowledge, the most likely candidate for a bacterial pathogen of whiteflies is Enterobacter cloacae, which can be ingested and grow to high densities in B. tabaci adults, causing mortality (31), though it is not known how commonly whiteflies encounter the bacterium. Other bacterial species have been implicated in causing low to moderate rates of mortality in whiteflies, though in many cases death appears to be caused by a toxic, bacterially produced compound rather than ingestion of the bacteria themselves (40,41). However, plant-associated insects, such as aphids and whiteflies, can encounter a variety of bacterial species while feeding on plants, and as this study has shown, these bacteria may have negative effects on the insects.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the most likely candidate for a bacterial pathogen of whiteflies is Enterobacter cloacae, which can be ingested and grow to high densities in B. tabaci adults, causing mortality (31), though it is not known how commonly whiteflies encounter the bacterium. Other bacterial species have been implicated in causing low to moderate rates of mortality in whiteflies, though in many cases death appears to be caused by a toxic, bacterially produced compound rather than ingestion of the bacteria themselves (40,41). However, plant-associated insects, such as aphids and whiteflies, can encounter a variety of bacterial species while feeding on plants, and as this study has shown, these bacteria may have negative effects on the insects.…”
Section: Discussionmentioning
confidence: 99%
“…Freedom Red (Paul Ecke Ranch, Encinitas, CA, USA), and eggplant cv. Millionaire Hybrid (Burpee) as described in Gelman et al (2002Gelman et al ( , 2005. The B. tabaci colony was maintained in a walk-in, climatecontrolled insect growth chamber (26 ± 2 o C, L:D 16:8, and RH of 60-80%).…”
Section: Insect Rearingmentioning
confidence: 99%
“…For rearing adults, the in vitro rearing system described by Salvucci and Crafts-Brandner (2000) was modified (Blackburn et al 2005) to monitor mean day survival of B. tabaci fed on artificial diets containing various sugars. Adults were anaesthetized with CO 2 and placed in rearing chambers ( Figure 1B) that were maintained in an incubator under conditions of 24±2 o C, RH of 40-60%, and L:D 16:8.…”
Section: Insect Rearingmentioning
confidence: 99%
“…are used as bio-pesticides in a number of countries. Toxins of P. luminescens and P. temperata caused mortality to caterpillars such as Galleria mellonella, Manduca sexta and Plutella xylostella upon injection (Duchaud et al 2003), while oral toxicity has been reported against Colorado potato beetle, sweet potato whitefly and mosquitoes (Blackburn et al 2005). However, the mechanism of insecticidal action of Photorhabdus toxins is still unclear.…”
Section: Introductionmentioning
confidence: 99%